The Effect of Celebrity Endorsement Towards Purchase Intention With Attitude Towards Advertisement as Mediation - Prastatia, Saskia Luftiara; , Dr. Anton Agus Setyawan, S.E., M.Si (2015)
Endorsement can be defined as an act of giving one's public approval or support to someone or something. A celebrity endorser is an individual who is known to the public (actor, sports figure, entertainer, etc) for his or her achievements in areas other than that of the product class endorsed. The purpose of this study is to analyze the effect of purchase intention of customer towards celebrity endorser with the mediation of customer's attitude towards advertisement. The population in this study is people who know JKT48 that endorsing Pocari Sweat and Honda Mio J with 200 samples using purposive sampling. The primary data required includes the results of the questionnaire data from the respondents. The analysis results physical attractiveness and source credibility were not supported while celebrity and brand congruence and attitude towards advertisement were supported.